DEFINITIVE AGRICULTURAL LAND’S PRICE FORMATION - PRAKANS. P, TOEY HUCTNER; ZARKOS NUZAL (International Journal of Multidisciplinary Research and Studies, 2021)
The land issue is strategically vital for any country, and in countries like Georgia it’s vitally vital. In the work below we concentrate attention on the issue of putting agricultural land in the international free market. The problem is analyzed in the condition of land price, land rent, demographic situation, agricultural subsidies, and so on. In conclusion, we represent an opinion that it is unacceptable to put Georgian agricultural land in international free turnover because the country can lose a significant part of agricultural land and the possibility of developing a profitable agricultural sector.